Comment on "Images of the vortex chain state in untwinned YBa2Cu3O7- delta crystals" - Barford, W; Harrison, M (1994)
A Comment on the Letter by P. L. Gammel et al. Phys. Rev. Lett. 68, 3343 (1992). © 1994 The American Physical Society.